Spectrum of Paediatric Endocrine Disorders: Experience from Bangladesh Shishu Hospital & Institute (Dhaka Shishu (Children) Hospital Journal, 2025)
Background: Paediatric endocrine disorders (PEDs) are on rising and assumed to be due to changing lifestyles, environmental pollutants, growing awareness, and improved diagnostic tools. Like developed countries, these noncommunicable diseases are coming forward day by day in our country warrant attention of health professionals. Objective: To describe the pattern and burden of Paediatric Endocrine Disorders that existing in recent years in our country. Methods: This is a descriptive, cross-sectional study conducted in Department of Paediatric Endocrinology & Metabolic Disorder including Indoor & OPD clinic of Bangladesh Shishu Hospital & Institute, Dhaka, Bangladesh over 4 years from January 2020 to November 2023. Data has been reviewed from previous records, noted on a format and analyzed using SPSS version 25. Results: Out of 645,058 new cases, a total of 3530 patients were seen at Endo-OPD with PEDs, accounts for 0.55% and 421 (11.9%) number of endocrine cases have been managed in indoor. Among admitted cases 224/53.2% male in contrast to 197/46.8% were female with ratio of 1.1:1, majority originates from urban area about 238/ 67.2%. The most common age of presentation was 1 to 5 years 35.9% though age ranged between 1st week to 18 years. Number of patients increased gradually from 2020 to 2023 with maximum on 2023, in OPD 1432/41% and indoor 200/49% cases. According to the International Classification of Pediatric Endocrine Diagnoses (ICPED) classification, combinedly calcium, phosphate metabolism and bone disorders were maximum (115/27.3%), and Vit D deficiency Rickets comprises 70% of them. But solely the top five admitted PEDs cases were thyroid disorders (82/19.47%), Rickets (77/18.3%), Adrenal gland disorders (48/11.4%), Obesity (42/9.9%) and short stature 38/9.0%. OPD case distribution of 2023 showed same pattern like majority were thyroid disorders 45.5%, followed by Rickets 13.54%, Adrenal disorder 7.33%, obesity 7.19% and Down syndromes with endocrinopathies 6.25%. Conclusion: Thyroid disorders, rickets, adrenal disorder and obesity ranked highest among the PEDs in our setting. There is a need to raise awareness of PEDs among healthcare professionals and the general population to improve early presentation to the clinic.DS (Child) H J 2023; 39(2): 106-114